(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In wireless sensor networks (WSNs), energy constraint of node is the major issue, as the sensor may be deployed in the area where energy backup or quick replacements may not be available. In such cases, preserving the node energy and prolonging the network life time play crucial role in wireless sensor networks. Similarly, sensor nodes are highly vulnerable to attacks, attackers can easily tamper the sensor node and compromise it. Thus to overcome above stated two problems, the proposed work ensures shortest path routing, which ensures network life time of sensor nodes and the trust based routing, which avoids node compromise attacks. The proposed shortest path routing algorithms takes route through multi-hop nodes to corresponding sink. The shortest path based on the geographical routing strategy chooses the nodes nearest to the routing node and sink node. The novel routing framework proposed in this work considered shortest path with trust based routes. The node’s energy is considered to taking reliable node on the routing path, which ensure the packet delivery and avoids any node failure due to less energy. The node’s trust value is evaluated with three type, which ensure that the paths created are more reliable